Prosody of the Word in Kazakh Ritual Song Rhythmics - Кuzbakova, Г.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The article is devoted to questions of interrelation of speech forms in Kazakh and folk musical and poetic art. The task is set to describe the conditionality of the temporary organization of song ritual genres by prosody of the Kazakh word. At a research analytical, komparativ methods of a research are used. The characteristic is given to rhythmic structure of early folklore forms of musical creativity of Kazakhs. Rhythmic forms of the Kazakh household and ceremonial songs were affected also by features of early folklore intoning and also the amount of national versification. The genres of Kazakh folklore, ritual wedding (betashar, toibastar, synsu), burial funeral cycles (jokta’u, zhyla’u), as well as songs related to the birth and childhood of the child (aldi-aldi, bessik zhyry, tussa’u kesu) are due to the art of syncretism of the word and melody. Various types of an accent in Kazakh – ascending and descending, accent and longitudinal have defined the quantitative nature of rhythmics of the Kazakh ceremonial genres. Singarmonizm in the Kazakh word is also considered from the point of view of influence on typology of rhythmic forms of the Kazakh ceremonial song.